Analisis Etos Kerja Pedagang Ikan Muslim Dalam Meningkatkan Kesejahteraan Keluarga Di Pasar Pulau Temiang Tebo - Rian Ivandri Hidayatullah; Ambok Pangiuk; Awal Habibah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Work ethic is the totality of an individual's personality in the context of work. Working is a form of self-dedication as a servant of Allah by obeying all His commands and avoiding all prohibitions. For this reason, Allah has provided facilities in the form of surface resources for human use in achieving their well-being. A strong work ethic can fulfill economic needs and desires within the family. Islam encourages its followers to work diligently and not to be lazy, as laziness can lead to poverty. The formation of a work ethic (including Islamic work ethic) is a complex process, involving various factors such as physical, biological, mental-psychological, socio-cultural, and possibly transcendental spiritual conditions and preconditions. This research adopts a qualitative approach and was conducted at the Padang Lamo Street Market, Pulau Temiang, Tebo Ulu District, Tebo Regency, in January 2023. The respondents in this study consisted of 27 individuals, including fish traders, consumers, and religious scholars. The findings of the research on fish traders in the Pulau Temiang Subdistrict Market, Tebo Regency, indicate that fish traders possess crucial work skills, exhibit diverse motivations such as earning a livelihood and pursuing hobbies, their work ethic is driven by the desire to meet their family's needs, and their economic conditions impact their well-being. Challenges include limited education, environmental conditions, and limited alternative job opportunities.